Content analysis of anashir lugoh (Arabic language structure) on the Ashab lugoh Instagram account: (@Ashab Lughah) تحليل محتوى عناصر اللغة في حساب إنستغرام أصحاب اللغة - Basri Btr, Mhd Hasan; Rahmaini (Institut Muslim Cendekia, 2025)
The development of social media has provided new opportunities for Arabic language learning, one of which is through the Instagram account @ashab.lugha. This study aims to analyze the content of Anashir Lugha displayed by this account, focusing on three main aspects: morphology (shorf), syntax (nahwu), and phonology (aswat). This research used a descriptive qualitative method with a case study approach, while data was obtained through documentation of posts in the form of feeds, reels, and Instagram stories relevant to Arabic language material. The results show that shorf content is presented by displaying changes in word form and variations in wazan in an easy-to-understand manner; nahwu content is the most dominant material, with explanations of i'rab, sentence structure, and word function; while aswat content focuses on practicing pronunciation of letters that sound similar but have different meanings. Based on these findings, it can be concluded that the @ashab.lugha account is able to present Arabic language structure material concisely, visually, and interactively, thus meeting the needs of digital learners and has the potential to become a non-formal learning medium that supports the formal learning process.